Stratified sampling applied to estimation of the volumetric fraction of alumina in cast metal matrix composites - Ranieri, K. [UNESP]; Costa, A. F.B. [UNESP]; Kiyan, C. [UNESP] (De Gruyter, 2009)
In this paper, we propose a statistic procedure for estimating theamount of alumina incorporated in aparticulated metal matrix compositesynthesized by the stir casting methodComposite specimens, consisting of A356AI alloy matrix material containing 5 wt°/o ofalumina particles, were prepared using thecompocast- ing technique. An intermediatetraversal section of each composite ingotwas stratified into 24 parts and thevolumetric fraction of alumina wasmeasured by image analysis at 279separate points to study the aluminadistribution in the material. Alumina particledistribution was observed to haveconsiderable heterogeneity. Thestratification technique employed in thisstudy permits an ideal trade-off between theaccuracy of the estimated alumina and therequired measurement labor. © CarlHanser Verlag, München.